Natural rubber/leather waste composite foam: A new eco-friendly material and recycling approach - Garcia, Nelissa Goncalves [UNESP]; Prado dos Reis, Elton Aparecido [UNESP]; Budemberg, Eduardo Roque [UNESP]; Silva Agostini, Deuber Lincon da [UNESP]; Salmazo, Leandra Oliveira [UNESP]; Cabrera, Flavio Camargo [UNESP]; Job, Aldo Eloizo [UNESP] (Wiley-Blackwell, 2015)
This article describes a new approach of recycling the leather waste (shavings) using it as filler in natural rubber foams composites. The foams were prepared using different amounts of leather waste (0-60 parts per hundred of rubber) and submitted to morphological (SEM microscopy) and mechanical analyses (cyclic stress-strain compression). The increase of leather shavings on the composite causes an increase of viscosity in the mixture, which reflects in the foaming process. This results in smaller and fairly uniform cells. Furthermore, expanded rubber has the biggest cell size, with more than 70% of cell with 1000 mu m, while the composite with the higher concentration of leather has around 80% of total number of cells with 100-400 mu m. The mechanical parameters were found to depend on the leather dust concentration. Moreover, the stiffness rises with the increase of leather shavings; consequently, the compression force for expanded rubber was 0.126 MPa as well as the composite with higher concentration of leather was 7.55 MPa. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41636.
Keywords: composites; elastomers; foams; recycling; rubber